Teaching Vocabulary Through Cartoon Movie of Seventh Grade Students to Increase Vocabulary Mastery - Komariah, Asri Nur; Usman, Sriati; Maf'ulah, Maf'ulah; Jamiludin, Jamiludin (Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary mastery is a crucial element of English learning because it enables students to communicate effectively in various contexts. However, many junior high school students still have limited vocabulary knowledge and low learning motivation, which creates a gap between expected learning outcomes and actual classroom practice. This study aimed to examine the effectiveness of using cartoon movies to improve the vocabulary mastery of seventh-grade students at SMP Negeri 12 Palu. This research employed a quasi-experimental design with a non-randomized control group using pre-test and post-test. The participants consisted of 30 students who were divided into experimental and control groups. Vocabulary tests were administered as the research instrument and the data were analyzed using descriptive statistics, the Wilcoxon Signed Ranks Test, and the Mann-Whitney U Test. The results indicated that students taught using cartoon movies showed a significant improvement compared to those taught using conventional methods. Thus, cartoon movies enhance vocabulary.